BCOR upregulation in a poorly differentiated synovial sarcoma with SS18L1‐SSX1 fusion—A pathologic and molecular pitfall. Issue 4 (4th January 2017) - Kao, Yu‐Chien; Sung, Yun‐Shao; Zhang, Lei; Kenan, Samuel; Singer, Samuel; Tap, William D.; Swanson, David; Dickson, Brendan C.; Antonescu, Cristina R.
Abstract : The diagnosis of poorly differentiated synovial sarcoma (PD‐SS) may be challenging due to overlapping morphologic features with other undifferentiated round cell sarcomas (URCS). Particularly relevant is the histologic overlap and shared BCOR overexpression between a subset of SS and URCS with various BCOR genetic abnormalities. Here, we report a case of PD‐SS lacking the canonical SS18‐SSX gene fusion, but showing strong BCOR immunoreactivity and BCOR gene abnormalities by FISH, which were misinterpreted as a URCS with BCOR gene rearrangements. The tumor had an unusual clinical presentation arising as an intraneural tumor in the ankle of a 29‐year‐old female. The tumor displayed a mixture of fascicular spindle cells and undifferentiated round cell components. FISH studies showed no SS18 gene abnormality; however, RNA sequencing identified a fusion transcript involving SS18L1 (a paralog gene of SS18 at 20q13.33) and SSX1 . Further FISH testing validated rearrangements in SSX1 and SS18L1 genes, in addition to complex structural abnormalities of the Xp11.22‐4 region. This is the second reported SS case harboring an SS18L1‐SSX1 alternative fusion variant, similarly occurring in association with a large nerve. The lack of SS18 gene rearrangements by FISH corroborated with the BCOR overexpression at both mRNA and protein level may result in diagnostic pitfalls with URCS with BCOR gene abnormalities. Our results further suggest that BCOR upregulation is emerging as a common downstream pathway for SS with either typical SS18‐SSX transcript or with rare fusion variants, such as SS18L1‐SSX . © 2017 Wiley Periodicals, Inc.